Comparison of the Effectiveness of Short-Term Psychodynamic Therapy and an Integrated Acceptance and Commitment–Based Therapy with Schema Therapy on Improving Interpersonal Relationships and Controlling Explosive Anger in Insecurely Attached Nurses with Anxiety Symptoms - Hassanezhad, Fatemeh; Shahabizadeh, Fatemeh; Jarrahi Feriz, Jalil (Journal of Assessment and Research in Applied Counseling (JARAC), 2026)
Objective: The objective of this study was to compare the effectiveness of short-term psychodynamic therapy and an integrated acceptance and commitment–based therapy with schema therapy on improving interpersonal relationships and controlling explosive anger in insecurely attached nurses with anxiety symptoms. Methods and Materials: This study employed a quasi-experimental design with pretest, posttest, and one-month follow-up, including a control group. The statistical population consisted of nurses working in intensive care, coronary care, emergency, and oncology wards of Imam Reza Hospital in Mashhad during the second half of 2024. Following a multistage screening process based on the Kian-Zadeh Adult Attachment Styles Questionnaire and the anxiety subscale of the DASS-21, 30 nurses with insecure attachment styles and elevated anxiety symptoms were selected and randomly assigned to three groups: short-term psychodynamic therapy, integrated acceptance and commitment–based therapy with schema therapy, and a wait-list control group (n = 10 per group). Each intervention was delivered in eight 70-minute sessions over four weeks. Data were collected using validated measures of interpersonal relationships and explosive anger at pretest, posttest, and follow-up. Data analysis was conducted using univariate and multivariate analyses of covariance and Bonferroni post hoc tests in SPSS-V22. Findings: Multivariate analysis of covariance revealed significant group effects for both interpersonal relationships and explosive anger at posttest and follow-up (p < .01). Bonferroni comparisons showed that both intervention groups significantly outperformed the control group on all outcomes. Short-term psychodynamic therapy demonstrated a significantly greater reduction in explosive anger at posttest compared to the integrated intervention (p < .05), while the integrated acceptance and commitment–based therapy with schema therapy showed a stronger effect on interpersonal relationships at posttest (p < .01). Differences between the two intervention groups were no longer significant at follow-up. Conclusion: Both short-term psychodynamic therapy and integrated acceptance and commitment–based therapy with schema therapy are effective interventions for improving interpersonal relationships and reducing explosive anger in insecurely attached nurses with anxiety symptoms, with differential short-term advantages across outcome domains.